PENGARUH BRAND AMBASSADOR, KEPERCAYAAN KONSUMEN DAN PROMOSI FLASH SALE MELALUI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PADA MARKET PLACE TOKOPEDIA - Nawangsari, Sri (Gapenas Publisher, 2024)
The aim of this research is to analyze the influence of brand ambassadors, consumer trust and flash sale promotions on purchasing decisions on the Tokopedia market place. And to find out which variables are most dominant in purchasing decisions on the Tokopedia market place. The analysis method for testing instruments and data in this research uses validity, reliability, normality, multiple linear regression, t test, f test, and coefficient of determination. The data used in this research is primary data with 100 respondents. The sampling method in this research is non-probability sampling with a purposive sampling technique. The results of this research show that the variables brand ambassador, consumer trust, and flash sale promotions influence purchasing decisions. And the most dominant variable in purchasing decisions is the flash sale promotion variable